Editorial: New insights into mechanisms of epigenetic modifiers in plant growth and development. Volume II - Luo, Ming; Sarnowski, Tomasz Jacek; Libault, Marc; Ríos, Gabino; Charron, Jean-Benoit; Mantri, Nitin; Zhang, Shoudong (Frontiers Media, 2023)
As we have learned, chromatin modifications, including histone modifications and DNA methylation, play a key role in plant development (Ng and Bird, 1999). However, accumulated evidence shows that, besides chromatin biochemical modifications, other epigenetic regulations such as chromatin architecture also function at a pivot point to regulate plant development (Zhang et al., 2021). In this Research Topic, five research papers describe multiple developmental facets mediated by different epigenetic mechanisms besides histone modifications. These manuscripts report experimental evidence or summarize recent advances in epigenetic regulations of some important developmental genes or development-related mechanisms. This Research Topic allows readers to learn of the latest advances in epigenetic regulations on seed germination, flowering time control, miRNA biogenesis and stability, secondary meristem maintenance as well as histone deacetylase 9 mediated day-length dependent hypocotyl cell elongation.